Research progress on influencing factors and assessment methods of pulp vitality - ZHU Xiao, CHEN Yanqi, QIAN Linna, JIANG Dingzhuo, SHI Ying, WU Zhifang (口腔疾病防治)
Healthy dental pulp is essential for preserving teeth and maintaining their normal function. Vital pulp therapy (VPT) is widely used in clinical applications because it aims to preserve vital pulp and enhance the long-term survival of teeth. An accurate diagnosis of pulp vitality is a prerequisite for successful VPT. However, accurately assessing pulp viability remains challenging in clinical practice. Pulp viability is influenced by various factors, including the type of pulp exposure, caries status, periodontitis, trauma, treatment factors, patient age, and individual differences. Assessing pulp viability requires a comprehensive consideration of medical history and clinical manifestations, along with a combination of various auxiliary methods, such as pulp sensibility tests, pulp blood flow tests, imaging techniques and molecular diagnostics. In the future, the technology for assessing pulp vitality should evolve toward chairside, visualization, and precision techniques, to achieve consistency between clinical and histological diagnoses, thereby providing patients with the most effective treatment.